New species of Hyperplatys Haldeman, 1847 and Urgleptes Dillon, 1956 (Coleoptera: Cerambycidae) from Mexico - Noguera, Felipe A.; Monné, Miguel A.; Toledo-Hernández, Víctor H.; Gutiérrez, Nayeli (Zootaxa, 2023)
Two new species of Acanthocinini (Lamiinae) from Mexico are described: Hyperplatys mexicanus sp. nov. from the state of Morelos; and Urgleptes martini sp. nov. from the states of Jalisco and Morelos.